Peningkatan Hasil Belajar Matematika Melalui Media Sedotan di Siswa Kelas I SDN Sarikarya - Wulandari, Tri; Utomo, Beni; Fatkhurahmah, Helviana (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
This study aims to improve the mathematics learning outcomes of addition and subtraction through concrete media in the form of straws for students in grade 1 SDN Sarikarya involving 22 students. The research method used is a class action research method using 2 cycles. Data collection techniques in this study were tests and observations. The results are in the form of data to then be analyzed through quantitative descriptive. The success criterion is that the percentage of learning completeness reaches> 75%. Based on the research conducted, it was found that the use of straw media showed an increase in mathematics learning outcomes in addition and subtraction material in each cycle. The percentage of students whose learning outcomes were completed at the pre-cycle stage was 50% with an average score of 66.3. In cycle I, it increased by 32% or was at 82% with an average value of 82.7. In cycle 2 there was an increase again with a percentage of 91% and a mean value of 86.8. These results indicate that the application of straw media makes students experience an increase in mathematics learning outcomes in addition and subtraction.